Respectful care during childbirth in health facilities globally: a qualitative evidence synthesis. (8th December 2017) - Shakibazadeh, E; Namadian, M; Bohren, MA; Vogel, JP; Rashidian, A; Nogueira Pileggi, V; Madeira, S; Leathersich, S; Tunçalp, Ӧ; Oladapo, OT; Souza, JP; Gülmezoglu, AM
Abstract : Background: What constitutes respectful maternity care (RMC) operationally in research and programme implementation is often variable. Objectives: To develop a conceptualisation of RMC. Search strategy: Key databases, including PubMed, CINAHL, EMBASE, Global Health Library, grey literature, and reference lists of relevant studies. Selection criteria: Primary qualitative studies focusing on care occurring during labour, childbirth, and/or immediately postpartum in health facilities, without any restrictions on locations or publication date. Data collection and analysis: A combined inductive and deductive approach was used to synthesise the data; the GRADE CERQual approach was used to assess the level of confidence in review findings. Main results: Sixty‐seven studies from 32 countries met our inclusion criteria. Twelve domains of RMC were synthesised: being free from harm and mistreatment; maintaining privacy and confidentiality; preserving women's dignity; prospective provision of information and seeking of informed consent; ensuring continuous access to family and community support; enhancing quality of physical environment and resources; providing equitable maternity care; engaging with effective communication; respecting women's choices that strengthen their capabilities to give birth; availability of competent and motivated human resources; provision of efficient and effective care; and continuity of care. Globally, women's perspectives of what constitutes RMC are quite consistent. Conclusions: This review presents an evidence‐based typology of RMC in health facilities globally, and demonstrates that the concept is broader than a reduction of disrespectful care or mistreatment of women during childbirth. Innovative approaches should be developed and tested to integrate RMC as a routine component of quality maternal and newborn care programmes. Tweetable abstract: Understanding respectful maternity care – synthesis of evidence from 67 qualitative studies. Tweetable abstract: Understanding respectful maternity care – synthesis of evidence from 67 qualitative studies.